Dicer‐Processed Small RNAs: Rules and Exceptions1. Issue 1 (16th November 2012) - Langenberger, David; Çakir, M. Volkan; Hoffmann, Steve; Stadler, Peter F.
Abstract Canonical microRNAs are excised from their hairpin‐shaped precursors by Dicer. In order to find possible exceptions to this rule and to identify additional substrates for Dicer processing we re‐evaluate the small RNA sequencing data of the Dicer knockdown experiment in MCF‐7 cells orignally published by Friedländer et al. [Friedländer et al., 2012, Nucleic Acids Res 40:37–52]. While the well‐known non‐Dicer mir‐451 is not sufficiently expressed in these experiments, there are several additional Dicer‐independent microRNAs, among them the important tumor supressor mir‐663a. We recover previously described examples of non‐miRNA Dicer substrates such as tRNA‐Gln and several snoRNAs. Interestingly, sdRNAs derived from box C/D snoRNAs are Dicer‐independent, while those derived from box H/ACA snoRNAs are often Dicer dependent. Several pol‐III transcripts, in particular the vault RNAs and the great ape specific snaRs are processed by Dicer, while the small RNAs originating from Y RNAs seem to be Dicer independent. J. Exp. Zool. (Mol. Dev. Evol.) 320B:35–46, 2013. © 2012 Wiley Periodicals, Inc.